Piano Sonata in A-flat major, op. 26 (Bote & Bock) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Ed. Bote & G. Bock; Germany; Berlin)
Early edition of the Piano Sonata no. 12 in A-flat major, op. 26, published in Berlin by Bote & Bock.